Expression and purification of the outer shell proteinVP2 of the 4th serotype Bluetongue virus, and preparation of monoclonal antibodies against this protein. (October 2017) - Zhou, Han; Li, Jiaxuan; Xie, Shuangyu; Zang, Mingxin; Xu, Yigang; Qiao, Xinyuan; Wang, Li; Jiang, Yanping; Cui, Wen; Li, Yijing; Tang, Lijie
Graphical abstract: VP2 protein of BTV-4 was expressed and used as immunogen to screen for mAb-secreting cells. Two cell lines (4A-1G7 and 4B-1B6) that could react with VP2 and recognize BTV-4 were obtained. Highlights: Expression and purification of VP2 segments of BTV-4. Obtaining two strains of monoclonal antibody recognizing BTV-4. Promising candidates for detecting BTV-4. Abstract: Bluetongue (BT) is an arbovirus transmitted disease by bites of the genus Culicoides and infects wild and domestic ruminants particularly in sheep. As an important outer shell protein which defines BTV serotypes, VP2 has been shown to be an ideal target antigen for identification of different BTV serotypes. In order to prepare a monoclonal antibody (mAb) against the VP2 protein of BTV-4, the corresponding encoding gene L2 was divided into three segments and then cloned into pET-28a (+) and pMAL-c5X vectors to generate recombinant plasmids, which were expressed in Escherichia coli BL21 (DE3) as histidine (His)-tagged (His-4A/4B/4C) and maltose-binding protein (MBP)-tagged (MBP-4A/4B/4C) fusion proteins. After affinity purification of His-4A/4B/4C with Ni-NTA agarose and MBP-4A/4B/4C with amylose resin, His-4A/4B/4C were used to immunize BALB/mice and MBP-4A/4B/4C were used to screen for mAb-secreting hybridomas. Five hybridoma cell lines stably secreting mAbs against different VP2 segments were obtained, in which 4A-1G7 and 4B-1B6 could recognize BTV-4 and also cross-react with other BTV serotypes. With the joint action of the two mAbs, BTV-4 and BTV-20 infection would be distinguished from other BTV serotypes. The successful preparation of recombinant VP2 segments and mAbs provides valuable materials that can be used in serological diagnosis of BTV-4.